THE X-RAY STUDY OF THE LIQUID AL-MN ALLOYS: UDC 539.266; 538.214 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The X-ray diffraction experiments for the liquid Al–Mn alloys was carried out in a wide concentration range at temperatures approximately 50 K higher than the liquidus temperature. The structure factors (SF) and radial distribution functions (RDF) of atoms were calculated from the X-ray scattering (MoKalpha) intensity curves. The analysis of X-ray data showed that the essential changes of local atomic structure of the liquid Al–Mn alloys was in Al-rich region. It have been established, that the concentration dependence of the nearest-neighbor distance is characterized by negative deviations from a linear. This fact denotes the priority of heteroatomic interaction in liquid binary alloys. The prepeak existence in the range from 9 to 25 nm-1 of diffraction vector values is the peculiarity of the obtained structure factor functions. The prepeaks caused by specific arrangement of atoms at distances of 0,4–0,5 nm in dependence of alloy composition.
Keywords: -